Government of Greenland
Greenland is the world’s largest island with an area of around 2.2 million sq. km, but only some 410,000 sq. km are not covered by ice. In June 2009 Greenland established the rule of Self Government what made the country partly independent from the Danish Kingdom. The website of the new Greenlandic government includes facts about the world´s biggest island and its political system, engagement in international affairs and trade.